Boosting the optical, structural, electrical, and dielectric properties of polystyrene using a hybrid GNP/Cu nanofiller: novel nanocomposites for energy storage applications - Al-Muntaser, A. A.; Pashameah, Rami Adel; Saeed, Abdu; Alwafi, Reem; Alzahrani, Eman; AlSubhi, Samah A.; Yassin, A. Y. (Journal of materials science. Materials in electronics, 2023)
In this work, graphene nanoplatelet (GNP) and copper nanoparticles (Cu NPs) were successfully incorporated into polystyrene (PS) via a solution casting approach, and a series of PS/GNP/Cu NPs nanocomposites were obtained. The present series’ structural, optical, and dielectric properties were deeply studied. The semicrystalline nature of the nanocomposites was affirmed by the X-ray diffraction (XRD) findings. The crystallite size (D) of Cu NPs was 4–27 nm, as reported in XRD analysis and confirmed by transmission electron microscopy (TEM). The optical absorption spectra were utilized to calculate some optical parameters such as optical energy gaps, refractive index, and band gap metallization criterion (M Eg ), where their values exhibited an enhancement in the optical properties of the nanocomposite films. Fourier transform infrared spectroscopic analysis (FT-IR) showed that the polymeric matrix and the GNP/Cu NPs hybrid nanofillers were complexed via hydrogen and coordination bonds. The AC conductivity and dielectric characteristics were investigated using broadband dielectric spectroscopy (BDS), which exhibited that the existence of the GNP/Cu NPs hybrid nanofillers significantly improved the charge/capacitive storage abilities of the prepared nanocomposites. Thus, the fascinating enhancement in AC conductivity and dielectric properties demonstrates the favorable applications of PS/GNP/Cu NPs nanocomposite films in flexible energy storage devices.